2008
DOI: 10.1002/ardp.200800026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Some 2,4,5‐Trisubstituted Thiazole Derivatives as Potential Antimicrobial and Anticancer Agents

Abstract: We report on the synthesis and biological evaluation of two series of 2,4,5-polysubstituted thiazoles comprising the acid hydrazide functionality and some derived pharmacophores known to contribute to various chemotherapeutic activities. All newly synthesized compounds were subjected to in-vitro antibacterial and antifungal screening. Of the compounds tested, 13 derivatives displayed inhibitory effect on the growth of three Gram-positive strains while they lack activity against Gram-negative bacteria. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…Moreover, thiazole derivatives are useful compounds for synthesis of biologically active agents like antimicrobial, 12 anticancer, 13,14 analgesic, and anti-inflammatory agents. 15 A large number of thiazole derivatives have potent anticancer activity and show selective activity against HeLa cancer cells.…”
Section: 11mentioning
confidence: 99%
“…Moreover, thiazole derivatives are useful compounds for synthesis of biologically active agents like antimicrobial, 12 anticancer, 13,14 analgesic, and anti-inflammatory agents. 15 A large number of thiazole derivatives have potent anticancer activity and show selective activity against HeLa cancer cells.…”
Section: 11mentioning
confidence: 99%
“…The 2-amino-1,3-thiazoles are biologically important compounds with a wide range of medicinal and biological applications including antibacterial, antifungal, anti-HIV, anti-hypertension, antiinflammatory, anticancer, anticonvulsant, and antidepressant [1][2][3][4][5][6]. Some 2-amino-1,3-thiazole derivatives have been reported as ligands of thrombopoietin [7,8], neuropeptide Y5 [9] and adenosine receptors [10,11] and as inhibitors of several physiological important enzymes like cyclindependant kinase [12], poly (ADP-Ribose) polymerase [13], urokinase [14] etc.…”
Section: Introductionmentioning
confidence: 99%
“…They are also useful as anti-allergic 13 , anti-inflammatory 14 and anthelmintic 15 agents and as appetite depressants 16 , intermediates for dyes 17 , plant protectants 18 , histamine H2antagonists 19 and photographic sensitizers 20 . On the other hand, careful literature survey revealed that thiazole, thiophene and pyrazole ring systems have occupied a unique position in the design and synthesis of novel biological active agents with remarkable analgesic and antiinflammatory activities [21][22][23] , in addition to their well documented potential antimicrobial activities [24][25][26][27] . Morever, thiazoles have found application in drug development for the treatment of hypertension 28 , schizophrenia 29 , HIV infections 30 , and as new inhibitors of bacterial DNA gyrase B 31 .…”
Section: Introductionmentioning
confidence: 99%